2018
DOI: 10.1124/dmd.118.081547
|View full text |Cite
|
Sign up to set email alerts
|

PBDEs Altered Gut Microbiome and Bile Acid Homeostasis in Male C57BL/6 Mice

Abstract: Polybrominated diphenyl ethers (PBDEs) are persistent environmental contaminants with well characterized toxicities in host organs. Gut microbiome is increasingly recognized as an important regulator of xenobiotic biotransformation; however, little is known about its interactions with PBDEs. Primary bile acids (BAs) are metabolized by the gut microbiome into more lipophilic secondary BAs that may be absorbed and interact with certain host receptors. The goal of this study was to test our hypothesis that PBDEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 62 publications
4
63
1
3
Order By: Relevance
“…We identified a total of 13,204 genes that were uniquely expressed by at least one of the four exposures groups, and that PBDEs activate both PXR and CAR pathways in human HepaRG cells. Consistent with the result in this study, previous studies have shown that PBDEs activate PXR/CAR pathways in mouse livers [21]. With regards to CAR pathway mediation, a previous study demonstrated the activation of CAR pathways through BDE-47 in human primary hepatocytes [12].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We identified a total of 13,204 genes that were uniquely expressed by at least one of the four exposures groups, and that PBDEs activate both PXR and CAR pathways in human HepaRG cells. Consistent with the result in this study, previous studies have shown that PBDEs activate PXR/CAR pathways in mouse livers [21]. With regards to CAR pathway mediation, a previous study demonstrated the activation of CAR pathways through BDE-47 in human primary hepatocytes [12].…”
Section: Discussionsupporting
confidence: 92%
“…With regards to the sirtuin signaling pathway, exposure to pollutants can affect SIRT1 expression; this can affect the expression of downstream proteins and result in toxic damage. Upregulation of SIRT1 expression is protective against the toxicity of pollutants [21]. In our current study, SIRT1 was significantly downregulated in HepaRG cells exposed to BDE-99, suggesting that this PBDE can leave hepatocytes vulnerable to toxic attacks.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…For example, 16S rRNA sequencing has been applied to study (i) the shift in intestinal microbiomes before and after drinking GT 4 and (ii) the impact of polybrominated diphenyl ethers, persistent environmental contaminants, on the regulation of primary bile acids metabolized by the mouse gut microbiome. 5 Although 16S rRNA sequencing has a relatively low cost per sample, there are many challenges associated with processing and interpreting the immense number of resulting DNA sequences. As is common for observational studies, it is often impossible to distinguish correlation from causation in microbiome surveys.…”
Section: Microbiome Surveys To Screen For Drug Effectsmentioning
confidence: 99%